Freezing of Swallowing. Issue 5 (18th January 2016) - Maetzler, Walter; Rattay, Tim W.; Hobert, Markus A.; Synofzik, Matthis; Bader, Angela; Berg, Daniela; Schaeffer, Eva; Rommel, Natalie; Devos, David; Bloem, Bastiaan R.; Bender, Benjamin
Abstract: View Supplementary Video 1 Background: Swallowing deficits and freezing phenomena represent severe parkinsonian features. Freezing as a symptom occurring during swallowing has not been reported on yet. Methods: We report on 3 patients with probable PSP‐parkinsonism (PSP‐P) who manifested freezing of swallowing (FOS). Results: All 3 patients experienced severe weight loss in recent months. At examination, 1 patient had freezing of gait. Video fluoroscopy showed nonfunctional trembling movements of the tongue and palate during chewing and volitional swallowing, with a 6‐ to 8‐Hz frequency that is typical for freezing episodes during walking and finger tapping. These freezing episodes were accompanied by impaired oral bolus transportation. The pharyngeal phase was not relevantly affected. Conclusions: FOS represents a novel disease feature of PSP‐P. The feature may have fundamental, but potentially treatable, consequences for patients' health and quality of life and may be considered in patients with degenerative parkinsonism who experience severe and unexplained weight loss. Abstract : View Supplementary Video 1